1995
DOI: 10.1161/01.cir.92.12.3415
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Importance of Central Effects of Atenolol and Metoprolol Measured by Heart Rate Variability During Mental Performance Tasks, Physical Exercise, and Daily Life in Stable Postinfarct Patients

Abstract: In stable postinfarct patients, chronic treatment with metoprolol and atenolol attenuates the reduction in HR variability induced by mental performance tasks, but the effects during exercise are limited. beta-Blockers do not appear to increase vagal tone in this stable patient group. The point of action in these patients is mainly a reduction in HR, probably due to a reduction in stress-induced sympathetic activation. Clinically significant differences between atenolol and metoprolol were absent, indicating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
1
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 36 publications
3
38
1
1
Order By: Relevance
“…The goal of treatment with atenolol will be a > 20% decrease in the mean heart rate, which reflects adequate beta blockade. 28,29 The average starting dose of losartan will be 0.4 mg/kg and the daily dose will be increased as tolerated by ∼0.4 mg/kg in each subsequent cycle to a maximum daily dose of between 1.0 and 1.4 mg/kg, not to exceed 100 mg.…”
Section: Study Treatmentsmentioning
confidence: 99%
“…The goal of treatment with atenolol will be a > 20% decrease in the mean heart rate, which reflects adequate beta blockade. 28,29 The average starting dose of losartan will be 0.4 mg/kg and the daily dose will be increased as tolerated by ∼0.4 mg/kg in each subsequent cycle to a maximum daily dose of between 1.0 and 1.4 mg/kg, not to exceed 100 mg.…”
Section: Study Treatmentsmentioning
confidence: 99%
“…Studies of situations in which mental or physical stress induces a reduction of HRV give support to this point of view (11,14). On the contrary, interventions that reduce the sympathetic outflow may induce an increase in HRV; this is the case for pharmacological maneuvers (15), some relaxation techniques (16)(17)(18) and, hypothetically, physical training (19). Conversely, a sedentary life style may induce a reduction in parasympathetic outflow paralleled by an increase in sympathetic outflow (20).…”
Section: Introductionmentioning
confidence: 96%
“…Similarly, recent evidence by Ablad et al (2007) obtained in anaesthetized rabbits suggested that β-blockers are acting centrally to increase cardiac vagal tone. In contrast, there are data obtained in normal human subjects 20,21 and in post-MI patients 22,23 indicating that the effects of β-blockers on vagal tone are likely to be due to their peripheral actions.…”
Section: Heart Failure Autonomic Control Of the Heart And Metoprololmentioning
confidence: 94%